Gigabit-capable passive optical networks - Hood, Dave, 1945-; Trojer, Elmar; IEEE Xplore (Online Service); Wiley (Hoboken : Wiley, 2012)
Enables engineers to better understand, implement, and comply with G-PON standards A passive optical network (PON) is a point-to-multipoint, fiber-to-the-premises network architecture in which unpowered optical splitters enable a single optical fiber to serve multiple premises. PONs consist of an optical line terminal at the service provider's central office and a number of optical network units near the end users. Compared with point-to-point architectures, PONs reduce the amount of fiber and central office equipment required. Gigabit-capable PONs (G-PONs) are today's access network sweet spot, optimized to deliver IPTV and other high-bandwidth services at a reasonable cost. G-PONs have been deployed in numerous networks across the globe, and the trends indicate higher growth for G-PONs than other PON technologies. Written by experts at the heart of G-PON development, standardization, and deployment, this text explains why the G-PON standards are what they are and how they impact the development of communication networks. It fully examines the historical development of the G-PON standards, pointing out alternatives and comparing them to other PON standards. The book begins with an introduction to the evolution of G-PON technology and standards. Next, it covers: . System requirements . Optical layer . Transmission convergence layer . Management . Services . Other technologies such as Ethernet PON, wireless broadband, and access migration This book not only examines current standards and technology, it also looks at evolving technology, discussing the advantages and disadvantages of various access networks currently under investigation. Gigabit-capable Passive Optical Networks is essential for all engineers responsible for developing and maintaining G-PONs, providing them with information and guidance they need to fully understand, implement, and comply with the standards.
Introduction -- System requirements -- Optical layer -- Transmission convergence layer -- Management -- Services -- Other technologies.
Includes bibliographical references and index.
Also available in print.
Mode of access: World Wide Web
Description based on PDF viewed 10/24/2017.
Keywords: Passive optical networks; Gigabit communications; Electronic books